The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/pts.2754
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of antimicrobial colorimetric pad for meat packaging based on polyvinyl alcohol aerogel with the incorporation of anthocyanins and silver nanoparticles

Abstract: A novel colorimetric pad with porous structure, good antimicrobial activity, and pHsensitivity has been developed based on polyvinyl alcohol (PVA), paper fibre, silver nanoparticles (AgNPs) and purple sweet potato anthocyanins (PSPA), aiming for the preservation and freshness indication of fresh meat. The effects of AgNPs content on the structure, physical properties and colour-changing behaviour in response to pH of the pad were investigated. The results showed that AgNPs physically interacted with polymer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Functional biopolymer-coated papers developed by Shankar and Rhim (2018) exhibited strong antimicrobial activity against foodborne pathogens (Listeria monocytogenes and E. coli) on fish mince, representing a biodegradable and environmentally friendly food packaging material. Innovative freshness pads developed by He et al (2023) showed significant effects in inhibiting microbial growth, reducing the production of volatile nitrogen compounds, and improving the sensory quality of meat. In recent years, a research focus has been encapsulating plant extracts or essential oil nanodispersions in edible coatings to delay the spoilage of meat products Wang et al, 2020;Zhang et al, 2020;Zhao et al, 2024).…”
Section: Meat and Seafood Packagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional biopolymer-coated papers developed by Shankar and Rhim (2018) exhibited strong antimicrobial activity against foodborne pathogens (Listeria monocytogenes and E. coli) on fish mince, representing a biodegradable and environmentally friendly food packaging material. Innovative freshness pads developed by He et al (2023) showed significant effects in inhibiting microbial growth, reducing the production of volatile nitrogen compounds, and improving the sensory quality of meat. In recent years, a research focus has been encapsulating plant extracts or essential oil nanodispersions in edible coatings to delay the spoilage of meat products Wang et al, 2020;Zhang et al, 2020;Zhao et al, 2024).…”
Section: Meat and Seafood Packagingmentioning
confidence: 99%
“…Meat and seafood packaging(Bian et al, 2023): Fabrication process of antimicrobial colorimetric pad for meat packaging (d); the changes of TVC, TVB-N, and pH of pork samples during storage and sensory analysis at 72 h (e); variations in the appearance of pork samples during storage (f). Ready-to-eat food packaging(He et al, 2023): Schematic of curcumin microencapsulated antioxidant paper (g). The physicochemical changes of cakes during 12 days at 25 • C: peroxide values, acid values, yeast, and mold count (h), and corresponding representative photographs (i).…”
mentioning
confidence: 99%
“…Thus, volatile and non-volatile antimicrobial compounds have been employed as antimicrobial agents for active food packaging. Particularly, polymeric materials with non-volatile compounds require direct contact with the food product (active polymer/food system) and include organic acids [ 4 ], peptides [ 5 ], enzymes [ 6 ] microorganisms such as yeasts or lactic bacteria [ 7 ], bacteriophages [ 8 ], Lauric arginate ethyl ester (LAE) [ 9 ], cationic polymers [ 10 ], and nanosized metal oxides [ 11 , 12 ]. Meanwhile, materials with volatile bioactive compounds can be easily released into the headspace as vapor or gas to inhibit microbial growth (active polymer/headspace/food system); direct contact with the food is not required, making them far more versatile and interesting for AFP design.…”
Section: Introductionmentioning
confidence: 99%